Contestations and complexities of nurses' participation in policy-making in South Africa - Ditlopo, P; Blaauw, D; Penn-Kekana, L; et al. (My University, 2014)
Background: There has been increased emphasis globally on nurses’ involvement in health policy and systems development. However, there has been limited scholarly attention on nurses’ participation in policy-making in South Africa. Objective: This paper analyses the dynamics, strengths, and weaknesses of nurses’ participation in four national health workforce policies: the 2008 Nursing Strategy, revision of the Scope of Practice for nurses, the new Framework for Nursing Qualifications, and the Occupation-Specific Dispensation (OSD) remuneration policy. Design: Using a policy analysis framework, we conducted in-depth interviews with 28 key informants and 73 frontline nurses in four South African provinces. Thematic content analysis was done using the Atlas.ti software. Results: The study found that nurses’ participation in policy-making is both contested and complex. The contestation relates to the extent and nature of nurses’ participation in nursing policies. There was a disjuncture between nursing leadership and frontline nurses in their levels of awareness of the four policies. The latter group was generally unaware of these policies with the exception of the OSD remuneration policy as it affected them directly. There was also limited consensus on which nursing group legitimately represented nursing issues in the policy arena. Shifting power relationships influenced who participated, how the participation happened, and the degree to which nurses’ views and inputs were considered and incorporated. Conclusions: The South African health system presents major opportunities for nurses to influence and direct policies that affect them. This will require a combination of proactive leadership, health policy capacity and skills development among nurses, and strong support from the national nursing association
PK
Keywords: Nurse's Role; Policy Making; South Africa